O012/#352 Atezolizumab and bevacizumab in recurrent endometrial cancer: a phase II, multi institutional trial. (4th December 2022) - Fuh, Katherine; Richardson, Debra; Arend, Rebecca; Mccourt, Carolyn; Hagemann, Andrea; Liang, Margaret; Holman, Laura; Washington, Christina; Walker, Joan; Mannel, Robert; Youn, Grace; Mutch, David; et al.
Abstract : Objectives: Clinical data across several solid tumors, including EC, suggests synergy between immune checkpoint inhibition and anti-angiogenic agents. This study sought to evaluate the efficacy and safety of Atezolizumab (A) and Bevacizumab (Bev) in recurrent EC. Methods: This multicenter, single arm trial (NCT03526432 ) enrolled patients with recurrent EC (1–2 priors) to receive A 1, 200 mg and Bev 15 mg/kg day 1 every 21 days. The primary endpoint was overall response rate (ORR) and duration of response (DOR). Results: There were 57 response evaluable patients who received both drugs for the first two cycles. Median age was 65 (25–91) years and race included 22.8% Black and 2% American Indian. 61% had endometrioid tumors, 18% UPSC or carcinosarcoma each and 4% clear cell. 87% were mismatch repair proficient (MMRp) and 13% MMRd. 15% had prior pelvic radiation. Adverse events and clinical activity in table 1 . Translational data including blood immune cell population analysis by CyTOF will be presented with the clinical data. Conclusions: The ORR for A and Bev approximates that seen with Len/Pem with far fewer side effects. An ongoing trial within the Alliance contains this similar arm and if confirmatory would support this combination as a treatment option.